Analysis of mechanism of budget financing of environmental protection - Komisaruk, N. О.; Комісарук, Н. О.; Комисарук, Н. А. (Одеса : Юрид. л-ра, 2014)
This article analyses the mechanism of budget financing of environmental protection and determines the features of the financial and economic system in the field of environmental protection.
Komisaruk N. О. Analysis of mechanism of budget financing of environmental protection / N. О. Komisaruk // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 73. – С. 97-101.
Keywords: budget financing; environmental protection fund; mechanism of budget financing; financial and economic system in the field of environmental protection; environmental tax; бюджетне фінансування; фонд охорони навколишнього природного середовища; механізм бюджетного фінансування; фінансово-економічна система в природоохоронній сфері; екологічний податок; бюджетное финансирование; фонд охраны окружающей природной среды; механизм бюджетного финансирования; финансово-экономическая система в природоохранной сфере; экологический налог